2004
DOI: 10.1002/pmic.200300771
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of post‐translational glycosylation and phosphorylation of proteins from the amino acid sequence

Abstract: Post-translational modifications (PTMs) occur on almost all proteins analyzed to date. The function of a modified protein is often strongly affected by these modifications and therefore increased knowledge about the potential PTMs of a target protein may increase our understanding of the molecular processes in which it takes part. High-throughput methods for the identification of PTMs are being developed, in particular within the fields of proteomics and mass spectrometry. However, these methods are still in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
1,513
1
18

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,838 publications
(1,554 citation statements)
references
References 80 publications
22
1,513
1
18
Order By: Relevance
“…One face of the horseshoe-shaped structure was completely devoid of any glycosylation (NetNGlyc 1.0 Server; Blom et al 2004). When the surface electrostatic potential of GrTLR3 was calculated with Deepview (Schwede et al 2003), the concave surface of the horseshoe-shaped structure and the glycosylation-free face were largely positively charged, which was consistent with its predicted interaction with dsRNA.…”
Section: Discussionmentioning
confidence: 54%
“…One face of the horseshoe-shaped structure was completely devoid of any glycosylation (NetNGlyc 1.0 Server; Blom et al 2004). When the surface electrostatic potential of GrTLR3 was calculated with Deepview (Schwede et al 2003), the concave surface of the horseshoe-shaped structure and the glycosylation-free face were largely positively charged, which was consistent with its predicted interaction with dsRNA.…”
Section: Discussionmentioning
confidence: 54%
“…In our study, both curcumin and PKC activator (PMA) cause SIP phosphorylation in MOLT-4 but not MOLT-4/AraG cells. Furthermore, NetPhosK (Blom et al, 2004) and KinasePhos (Huang et al, 2005) programs predict the Ser141 residue of SIP as the phosphorylation site of Figure 6 The Ser141Ala mutation attenuates the nuclear accumulation and the apoptosis-promoting effect of SIP in different cells treated with diverse apoptosis stimuli. The indicated cells were transfected with plasmids expressing EGFP-fused wild-type or mutant SIP for 24 h, incubated for 12 h with 25 mg/ml etoposide (ETO), 500 ng/ml doxorubicin (DOXO), 25 mM nitro mustard (NM), 100 J/m 2 ultraviolet irradiation (UV) or 35 mM curcumin (CUR), then applied to analyses for SIP localization and cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that in Xenopus melanopsin's conspicuously long cytoplasmic tail contains potential phosphorylation sites, suggesting that its activation state may be regulated by kinases (Provencio et al, 1998). By using an algorithm of NetPhos (Blom et al, 2004), we found that chicken cOpn4-a has 33 predicted phosphorylation sites in the cytoplasmic tail, while a truncated melanopsin, cOpn4-b, has 19 sites in the cytoplasmic region. Thus, it is likely that cOtn4-b may have a lower activity than cOpn4-a, or that these two forms of melanopsin may be differentially regulated by certain kinases.…”
Section: Two Types Of Chicken Melanopsin Mrna Are Expressed During Dementioning
confidence: 90%